Addressing the Issue of the Decline in Nurses in Pakistan - Ashiq Ali, Anny (Journal of Liaquat University of Medical & Health Sciences, 2023)
The shortage of nurses is a global issue harming the international healthcare system. According to the WHO, Health care nurses deficiency is assessed to be 7 million and is anticipated to reach 12.9 million by 20351. Around 57 countries in the mainstream continent of Africa, and Asia, were facing severe healthcare worker crises2. Thus policies should be made to cover this ratio of shortfall in Pakistan. Concerns are articulated by the authors about the shortage in nursing, nursing downsizings, decreasing student admissions, faculty leavings, the ageing workforce, and worldwide hiring. Some of the reasons for these concerns are Poor management and infrastructure of the hospitals, low wages, lack of recognition of the values of nursing as a profession, scarce resources in education and clinical settings, medical dominance, and limited opportunities for career advancement, these all factors contribute to powerlessness and harassment among nurses, working in Pakistan. Thus, these are considered the main reasons for the migration of nurses to our country. In Pakistan, the management has paid little attention to developing an approach for nursing personnel. Thus, the passage of Pakistani-educated nurses overseas has an undesirable effect and has already damaged our healthcare system.